The Role of Women in the Family as Mompreneur According to Islamic View - Neni Komalasari; Mubair Agustin (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2022)
The role of women in the family plays an important and diverse role. Not just as a wife or a mother to her children. Women play the role of financial regulators in the family. With the role of financial regulator in the family, women in the era of digitalization are increasingly sensitive to the business world. Women are starting to have a lot of creativity to be entrepreneurial. This is done not only as a favorite but a variety of motivations as well as a large role as a regulator of economic sovereignty in the family. Entrepreneurial motivation in women includes motivation from within which includes the desire to be independent. Women in entrepreneurial families are called Mompreneurs. Mompreneur comes from the word mom and entrepreneur. The purpose of mompreneur is a mother who is a business or entrepreneurial but still does not abandon her role as a housewife. With his role, is it good according to islamic view? While the main task of women in the family is to educate children and accompany husbands and perform other domestic tasks,not as a breadwinner, from the study of literature on the view of Islam in emancipation. Emancipation that respects women's rights equals that of men. The role of women as mompreneur has positive values and is very beneficial to reduce the number of unemployed, support family welfare, mobilize self-reliance for other women in sociaty and contribute to the country and religion.